Progress, Truth and Historical Perspective in Damián Hudson's Recuerdos Históricos de Cuyo, 1864-1874. An Approach to the Origins of Rioplatense Scholarly Historiography (2023)
In this article, we analyze a series of philosophical ideas and interpretive perspectives that Damián Hudson, from Cuyo, used to construct his work Recuerdos históricos sobre la provincia de Cuyo (1864-74), a work that we inscribe at the beginning of Argentine scholarly historiography. We will explore his idea of progress, a concept that he identifies with providence, an incremental historical power that displays a universal development that advances humanity and the Nation towards well-being and development. This sense of history would embody a historical truth that it is the duty of those who study the past to reveal, but not by way of value neutrality, but by critically positioning themselves in and philosophically reflecting on the processes of provincial and national historical development. We close with some reflections on the interpretative intersections that occur between history as a process and written history as an intellectual exercise, concepts that tend to be combined at the time.